TECHNOLOGY OF FORMATION OF AKMEOLOGICAL POSITION IN FUTURE TEACHERS - Parmonov Akmal Abdupattaevich (Scholar Express Journal, 2021)
This article is based on the current content of the formation of acmeological position in future teachers, the improvement of modern requirements for pedagogical personality, the full implementation of research results in this field, the possibilities of training specialists in pedagogical universities and the diagnosis of the current situation. attempts have been made to disclose the full implementation processes as a problem of the subject.
Keywords: Acmeological Position; Ability development; knowledge; skills